ZnO Nanopillar Coated Surfaces with Substrate‐Dependent Superbactericidal Property. Issue 14 (22nd February 2018) - Yi, Guangshun; Yuan, Yuan; Li, Xiukai; Zhang, Yugen
Abstract: ZnO nanopillars coated on various surfaces are able to kill adhered bacteria and fungi due to their physical structure through a rupturing mechanism. Remarkably, zinc foil and galvanized steel surfaces with ZnO nanopillar coatings demonstrate an excellent remote bacteria‐killing property. Their bacterial killing efficacy is several orders higher than ZnO nanopillars coated on other surfaces as well as ZnO nanoparticles themselves. Mechanistic study shows that the nanostructure surface kills adhered microbial cells by rupturing the cell wall, while superoxide ( O2 − ) released from the ZnO coating with electrons donated from zinc via the Zn/ZnO interface rather than photoirritation is responsible for the superior remote killing. The results of this study represent a novel mechanism of surface disinfection and its application in water disinfection is also demonstrated. Abstract : ZnO nanopillar coated zinc demonstrates an excellent remote bacteria‐killing property which kills adhered microbial cells by rupturing the cell wall with surface nanostructures and kills remote disattached cells via superoxide ( O2 − ) radicals. The source of radical release is due to electrons donated from zinc via the Zn/ZnO interface rather than photoirritation.